2014
DOI: 10.1111/jam.12499
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus salivarius Ren prevent the early colorectal carcinogenesis in 1, 2-dimethylhydrazine-induced rat model

Abstract: Aims: The objective of this study was to investigate the impact of Lactobacillus salivarius Ren (LS) on modulating colonic micro flora structure and influencing host colonic health in a rat model with colorectal precancerous lesions. Methods and Results: Male F344 rats were injected with 1, 2-dimethylhydrazine (DMH) and treated with LS of two doses (5 9 10 8 and 1 9 10 10 CFU kg À1 body weight) for 15 weeks. The colonic microflora profiles, luminal metabolites, epithelial proliferation and precancerous lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 35 publications
1
51
0
2
Order By: Relevance
“…ACF was detected in DMH-treated animals after 16 weeks in our previous study (Zhu et al, 2014). Some strains such as Bacteroides sp.…”
Section: Shifts Of Critical Variable Strains During Tumorigenesismentioning
confidence: 57%
See 2 more Smart Citations
“…ACF was detected in DMH-treated animals after 16 weeks in our previous study (Zhu et al, 2014). Some strains such as Bacteroides sp.…”
Section: Shifts Of Critical Variable Strains During Tumorigenesismentioning
confidence: 57%
“…In our previous study, we demonstrated that Ren could modulate colonic microflora and therefore prevent early colorectal carcinogenesis in a DMH-induced rat model (Zhu et al, 2014). However, it was unclear if such an effect is apparent in CRC development.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A maioria dos animais teve o câncer de cólon induzido por DMH (Brasil, 2012, Kumar et al 2012, Zhu et al 2014 Urbanska et al (2009) verificaram que para os camundongos tratados L. acidophilus, o peso corporal manteve-se constante durante 17 dias em relação ao grupo de animais controle, minimizando a inflamação intestinal e retardando a progressão de adenomas. Kumar et al (2012) observaram que uso de L. plantarum na alimentação dos animais tratados resultou em um aumento significativo no ganho de peso em comparação ao grupo não tratado.…”
Section: Redução Do Câncer De Cólonunclassified
“…Os ACF induzidos por DMH são estabelecidos como um substituto biomarcador de câncer de cólon, considerando sua alta correlação com a carcinogênese e sua recapitulação de características patológicas e moleculares de pacientes potenciais com este câncer (Zhu et al 2014). O câncer de cólon induzido por DMH experimental em ratos é um processo prolongado de múltiplos estágios, apresentando características de cinética celular, molecular e histopatoló-gica da tumorigênese que imita o câncer colorretal humano (Kumar et al 2012).…”
Section: Introductionunclassified